Human trafficking, human misery : the global trade in human beings - Aronowitz, Alexix A. (New York ; Washington ; London Praeger, 2009)
Virtually all countries in the world are affected by the scourge of human trafficking, either as a source, transit, or destination country, or combination thereof.
Keywords: Pobreza -- Aspectos sociales; Prostitución; Derechos humanos; Tráfico de personas